Wild things : a novel - Kay, Laura, 1989- (Vintage Books, a division of Penguin Random House LLC, 2023)
"El is in a rut. She's been hiding in the photocopier room at the same dead-end job for longer than she cares to remember, she's sharing a flat with a girl who leaves passive-aggressive smiley face notes on the fridge about milk consumption and, worst of all, she's been in unrequited love with her best friend, effortlessly cool lesbian Ray, for years. So when a plan is hatched for El, Ray, and their two other closest friends--newly heartbroken Will and karaoke-and-Twilight-superfan Jamie--to ditch the big city and move out to a ramshackle house on the edge of an English country village, it feels like just the escape she needs. Despite being the DIY challenge of a lifetime, the newly named Lavender House has all the makings of becoming the queer commune of the friends' dreams. (Will has been given a pass as the gang's Token Straight.) But as they start plotting their bright new future and making preparations for a grand housewarming party to thank the surprisingly but wonderfully welcoming community, El is forced to confront her feelings for Ray--the feelings that she's been desperately trying to keep buried. Is it worth ruining a perfectly good friendship for a chance at love?"--